2019
DOI: 10.1007/s00167-019-05410-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and ethnic polymorphism render prosthetic overhang and under-coverage inevitable using off-the shelf TKA implants

Abstract: Purpose Unexplained pain and stiffness after total knee arthroplasty (TKA) often result from mismatch between implant geometry and knee morphology, which depends on patient size, sex, and ethnicity. This study aimed to determine whether size, sex, or ethnicity are independently associated with distal femoral morphology in healthy Caucasian and Asian knees, and to compare anatomic ratios to those of commercially available TKA implants. Methods Two series of computed tomography (CT) angiograms from France (264 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 38 publications
2
56
0
1
Order By: Relevance
“…Although our patients were quite the same ethnic groups, this algorithm only achieved 23% correct femoral size in our patient group. We only deduced in the past that the knee anatomy differs between Caucasian and Asian population groups [ 21 , 22 , 23 ]. However, even in similar populations, height- and gender-based criteria seemed to have unsatisfactory accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Although our patients were quite the same ethnic groups, this algorithm only achieved 23% correct femoral size in our patient group. We only deduced in the past that the knee anatomy differs between Caucasian and Asian population groups [ 21 , 22 , 23 ]. However, even in similar populations, height- and gender-based criteria seemed to have unsatisfactory accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to find in the patients' sex the explanation for unsatisfactory clinical results after TKA. 10,11 This study's main objective was to evaluate the possible sex differences in the shape of the distal femur. The secondary objective was to assess whether there is an age group influence on morphometry.…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to ML undercoverage and overcoverage, respectively, when TKA components based on the femurs of Caucasian patients are used. Moreover, the prostheses of conventional TKA cannot cover the wide spectrum of ethnic tibiofemoral morphotypes [25]. Mismatch in the angles of the sulcus between the native knees and prostheses has been proved, however, it is not clear to what extent this is true for other patellofemoral ratios [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the prostheses of conventional TKA cannot cover the wide spectrum of ethnic tibiofemoral morphotypes [25]. Mismatch in the angles of the sulcus between the native knees and prostheses has been proved, however, it is not clear to what extent this is true for other patellofemoral ratios [25,26]. In recent studies, it was shown that four of the five measured trochlear morphometric parameters relied significantly on ethnicity, whereas only two of the measured parameters relied on gender [26].…”
Section: Introductionmentioning
confidence: 99%